2017
DOI: 10.1007/s12185-017-2362-6
|View full text |Cite
|
Sign up to set email alerts
|

A new prognostic score comprising lactate dehydrogenase, albumin and neutrophil to lymphocyte ratio to predict sensitivity to first-line chemotherapy in patients with peripheral T-cell lymphomas

Abstract: No standard therapy for peripheral T-cell lymphomas (PTCLs) has been established, and treatment outcomes are poor. Upfront stem cell transplantation has been investigated in several studies, some of which have reported promising outcomes. However, some patients maintain long-term remission after chemotherapy alone. It is thus important to predict sensitivity to first-line chemotherapy to optimize treatment strategies. In the present study, we retrospectively analyzed time to treatment failure (TTF) of first-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
1
14
0
1
Order By: Relevance
“…Moreover, patient follow-up duration influences NLR, as illustrated by the fact that the largest differences observed across patient prognostic groups occur within the first 12 months of follow-up (11). Beside confirming the baseline prognostic value of NLR, its early decrease following only one cycle of chemotherapy appears to be of good prognosis in multiple pathologies: (i) colorectal cancer (13, 14); (ii) mesothelioma; (iii) triple-negative breast cancer (15); (iv) docetaxel-treated patients bearing lung, prostate, head and neck or breast cancers (16); (v) advanced pancreatic adenocarcinoma; and (vi) in peripheral T-cell lymphomas (17).…”
Section: Circulating Neutrophils In Cancermentioning
confidence: 99%
“…Moreover, patient follow-up duration influences NLR, as illustrated by the fact that the largest differences observed across patient prognostic groups occur within the first 12 months of follow-up (11). Beside confirming the baseline prognostic value of NLR, its early decrease following only one cycle of chemotherapy appears to be of good prognosis in multiple pathologies: (i) colorectal cancer (13, 14); (ii) mesothelioma; (iii) triple-negative breast cancer (15); (iv) docetaxel-treated patients bearing lung, prostate, head and neck or breast cancers (16); (v) advanced pancreatic adenocarcinoma; and (vi) in peripheral T-cell lymphomas (17).…”
Section: Circulating Neutrophils In Cancermentioning
confidence: 99%
“…Based on studies of the tumor microenvironment, the prognostic role of the NLR in PTCL has attracted more attention in recent years. On multivariate analysis in 59 patients with PTCLs for time to treatment failure (TTF), high NLR was extracted as adverse prognostic factors (HR = 2.25, 95% CI 1.23–4.10, P = 0.008) [ 28 ]. Zhao et al [ 29 ] conducted a retrospective study of 213 adult PTCL patients and assessed the prognostic role of the NLR in the CR and survival of PTCL patients, and univariable analysis indicated that the NLR was correlated with worse OS.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil count and LDH both routinely detected the hematological index and were easily available in our clinical practice. Previous studies have investigated the prognostic value of LDH level, neutrophil count, and NLR in many solid tumors (10,21,24). However, there was no investigation about the role of the LDH level combined with neutrophil count or NLR in the prognosis of ESCC patients treated with radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the predictive value of neutrophil count in the prognosis of ESCC patients treated with radiotherapy is still unclear. Recently, the prognostic value of LDH has been widely investigated in various cancers, such as metastatic renal cell carcinoma (17), breast cancer (18), nasopharyngeal carcinoma (19), prostate cancer (20), lymphoma (21), non-small cell lung cancer (22), and ESCC (23,24). Although LDH and neutrophil count are reliable prognostic predictors, it is still not clear whether they can be combined together in a prognostic risk score model to predict the prognosis of ESCC patients treated with radiotherapy.…”
Section: Introductionmentioning
confidence: 99%